Analisis Tingkat Kesehatan Bank Syariah yang Terdaftar di Bursa Efek Indonesia (BEI) dengan Metode RGEC - Rusman Azizoma Rusman Azizoma; Hariono; Sri Mulya Hastuti (Universitas Islam Negeri Mataram, 2026)
To give a complete picture of how resilient and adaptable Islamic banks are to major shifts in the economy, research on the state of health of Indonesian Islamic banks prior to, during, and following the COVID-19 pandemic is crucial. Analyzing the state of Islamic banks' health prior to, during, and following the COVID-19 epidemic is the goal of this study. Using purposive sampling and the criteria of releasing financial reports to the public prior to, during, and following the COVID-19 epidemic, the study employs a descriptive quantitative approach with a population of Islamic banks' financial reports filed on the Indonesia Stock Exchange. Financial ratio analysis is the data analysis method used in this study to evaluate bank financial performance utilizing the RGEC method. The findings of the study indicate that, based on the RGEC analysis, Bank BTPN Syariah is a healthy bank overall, making it highly resilient to adverse effects from external variables and condition changes. However, because Bank Panin Dubai Syariah is categorized as unhealthy, it is thought to be less resilient to major adverse effects from shifting circumstances and other outside forces.